2017
DOI: 10.1158/0008-5472.can-16-1204
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-Dependent Repression of ERRγ Reprograms Metabolism in Prostate Cancer

Abstract: How androgen signaling contributes to the oncometabolic state of prostate cancer remains unclear. Here, we show how the estrogen-related receptor γ (ERRγ) negatively controls mitochondrial respiration in prostate cancer cells. Sustained treatment of prostate cancer cells with androgens increased the activity of several metabolic pathways, including aerobic glycolysis, mitochondrial respiration, and lipid synthesis. An analysis of the intersection of gene expression, binding events, and motif analyses after and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 46 publications
4
60
1
Order By: Relevance
“…Although AR is recruited to the regulatory regions of many of the genes involved in these metabolic processes, numerous androgen-sensitive genes are not direct AR transcriptional targets (Audet-Walsh et al 2017) but were identified in our study as direct targets of mTOR ( Fig. 4; Supplemental Fig.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Although AR is recruited to the regulatory regions of many of the genes involved in these metabolic processes, numerous androgen-sensitive genes are not direct AR transcriptional targets (Audet-Walsh et al 2017) but were identified in our study as direct targets of mTOR ( Fig. 4; Supplemental Fig.…”
Section: Discussionmentioning
confidence: 68%
“…The central role played by AR in the development and progression of PCa is well appreciated, including its role in reprogramming mitochondrial metabolism (Tennakoon et al 2014;Audet-Walsh et al 2017). Although AR is recruited to the regulatory regions of many of the genes involved in these metabolic processes, numerous androgen-sensitive genes are not direct AR transcriptional targets (Audet-Walsh et al 2017) but were identified in our study as direct targets of mTOR ( Fig.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Loss of ESRRG has previously been implicated in other malignancies including prostate cancer where it impacts proliferation (52,53). ESRRG has also been implicated in breast cancer.…”
Section: Discussionmentioning
confidence: 99%